Bicycle network needs, solutions, and data collection systems: A theoretical framework and case studies. Issue 2 (June 2022) - Reggiani, Giulia; Salomons, A. Maria; Sterk, Merel; Yuan, Yufei; O'Hern, Steve; Daamen, Winnie; Hoogendoorn, Serge
Highlights: A framework to relate the 'bicycle network needs' of cities with data collection systems. Two case studies show the needs, solutions, and data collection systems in different bicycle contexts. Bicycle ignorant cities focus on safety and trip data as a starting point for their cycling network planning. Bicycle-friendly cities focus on comfort needs and collect data related to the real-time use of the network. Abstract: Similarly to Maslow's pyramid of human needs, we theorize that cities have a pyramid of bicycle network needs that depends on their level of bicycle culture. As an increasing number of data sources emerge for bicycle data collection, transport authorities face the challenge of understanding how to use the data and which data sources are fit for their network needs. This article defines a framework that relates the bicycle network needs of cities with data collection systems. We showcase the need-driven framework through a case study of Melbourne, Australia, a bicycle ignorant city, and surveying 15 municipalities (and their consultancies) of the Netherlands. By using the proposed need-driven framework cities can understand how to fully exploit bicycle data collection systems and make a systematic plan.